ENRICHMENT OF SYSTEMS THINKING FOR PROBLEM SOLVING IN ENGINEERING SYSTEMS USING THE HERMENEUTIC LOOP: CASE STUDIES FOR DESIGNERS IN THE FIELD OF REMOTE COMMUNICATION (Malaysian Management Journal, 2024)
The systems thinking approach to problem solving is a dynamic and productive approach. However, emphasizing only the objective aspects of a phenomena and neglecting their subjective aspects can decrease its problem solving power. In order to enhance the problem solving power of systems thinking, it is proposed in this article to enrich systems thinking by using the hermeneutic loop. This applied research adopts practical aspects of systems thinking and hermeneutics in understanding and solving problems more effectively. The proposed approach is comprised of an additive loop, named the hermeneutic loop, concerning simultaneously “the whole system and its parts” and “subjectively and objectively”. Requirements of systems thinking are highlighted involving the holism and life cycle of the system. A summary of the considerations for systems thinking regarding holism and lifetime are as follows: (1) feedback in lifetime, (2) feed forward, (3) combining human and tools, (4) resources, (5) stock and flow and (6) carrying capacity (saturation). The utilization of this enriched systems thinking is investigated in three real engineering design processes, including case studies for designers in the field of remote communication. As the result, the proposed enriched systems thinking provides an improved understanding of the whole, which improves the solving power of the designers of components, and adds subjective product design to the objective design.